Massive intraperitoneal hemorrhage due to spontaneous rupture of hepatocellular carcinoma: Case report - Mustafa YILMAZ; Cihat TETİK and Nadir YÖNETÇİ and Uğur SUNGURTEKİN (Turkish Journal of Gastroenterology, 2019)
-